Relationship between fish consumption and nutritional status and learning achievement of vocational high school students in Mejayan Village, Madiun Regency - Haendra Kusuma Putra Ashad; Agnes Puspitasari Sudarmo; Abdul Kohar Mudzakir (Nekton, 2025)
Vocational High School (SMK) is a secondary school that aims to produce quality human resources for those who are ready to work at a productive age. SMK-level schools are inhabited by teenage children at the age–15-17 years. Teenagers at that age need adequate nutritional intake, both in quality and quantity, for their growth and development, both in terms of health and non-health. Fish is a food ingredient with a variety of health and non-health benefits. The health benefits of fish are in the form of good nutritional status, while in the non-health aspect, it improves cognitive aspects in the form of learning achievements at school. This study aimed to investigate the relationship between fish consumption, nutritional status, and learning achievement among vocational students in Mejayan Village. The study used a cross-sectional design with 177 students, and data were collected through questionnaires, anthropometric measurements of IMT/U, food recall 1 × 24 hours, and report card scores. Data analysis using the Chi-Square method The results showed that the fish consumption level of vocational high school students in Mejayan Village was low at 8.18 kg/capita/year and there was no significant relationship with nutritional status (p=0.911) or learning achievement (p=0.422). The absence of a relationship between the two variables may be due to factors other than fish consumption that influence the results. Based on this research, education on the importance of fish consumption for students is needed to increase the benefits of their nutritional and cognitive status.